Production of High-Quality Seeds in Eryngium foetidum: Optimizing Post-Harvest Resting Conditions for Sustainable Unconventional Food Systems - Laura Monteiro Pedrosa; Isabelle Caroline Bailosa do Rosário; Giovanna de Castro; Cibele Chalita Martins (Agronomy)
Eryngium foetidum is a promising crop for diversifying agriculture and supporting sustainable development through nutrient-rich unconventional foods. However, limited knowledge about its seed viability and post-harvest management hinders its commercial scalability. This study explored the effects of post-harvest resting treatments on seed quality and vigor, assessing seeds from whole plants, aerial parts, floral spikes, and umbels after 7 and 14 days of resting. Key metrics included seed yield, purity, moisture content, germination, and vigor were assessed. Results showed that seeds retained on whole plants achieved the highest physical purity (72.2%). Seeds that rested for 7 days exhibited higher germination rates (59%), faster germination (mean germination time of 17 days), and improved seedling establishment (70% emergence) compared to seeds that rested for longer durations. These outcomes highlight the importance of specific post-harvest conditions for optimizing assimilate redistribution enhancing seed quality and seedling performance. This research bridges a critical gap in post-harvest management knowledge for E. foetidum, offering practical insights to improve cultivation practices and promote its adoption as a strategic crop. The findings align with global efforts to advance sustainable and innovative agroecosystems. Further studies under diverse environmental conditions and harvest times are recommended to validate these results and support large-scale implementation.